Strengthening the Value of Religious Moderation in Islamic Boarding Schools - Zakariyah Zakariyah; Umu Fauziyah; Muhammad Maulana Nur Kholis (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2022)
This article aims to describe and determine the value of moderation and the implementation of the value of moderation in Islamic education at the Al-Fattah Siman Islamic Boarding School Sekaran Lamongan. This article uses a descriptive qualitative research design. The study’s data collection methods were interviews, observation, and documentation studies. Data were analyzed using descriptive analysis. The results of the research on the implementation of moderation values ​​in Islamic education at the Al-Fattah Siman Islamic Boarding School Sekaran Lamongan show that; 1) Understanding the values ​​of moderation in Islamic education is the basis for the formation of the character of the santri who in practice adheres to the principles of Ahlussunnah waljama’ah understanding with a tendency to moderation or wasaţiyyah through understanding Aqedah, sharia. or worship and morality. 2) The implementation of moderation values ​​in Islamic education is carried out in several stages, namely planning, implementation and evaluation. 3) The implementation of the values ​​of moderation in Islamic education at the Al-Fattah Siman Islamic Boarding School Sekaran Lamongan is applied to three activities, namely teaching and learning activities, religious-spiritual activities, and skills supporting activities; 4) The implementation of moderate values ​​in Islamic education uses four strategies, namely introduction, habituation, example, and practice; 5) Evaluation of the implementation of moderation values ​​in Islamic education is divided into three forms, namely program evaluation, evaluation of the learning process and evaluation of learning outcomes.